Study of feto-maternal outcome in patients of jaundice in third trimester of pregnancy - Patel, Brijesh J.; Thaker, Rajal V.; Shah, Jagruti M.; Mewada, Bhavna N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Jaundice in pregnancy is an important medical disorder, more commonly seen in developing countries than developed ones. It comprises of a formidable list of complications that may adversely affect the pregnant woman and her fetus. Objective of current study was to study causes and feto-maternal outcome in pregnancies with jaundice in 3rd trimester. Methods: This was a retrospective study of 49 patients admitted in department of Obstetrics & Gynaecology at a tertiary care hospital with jaundice in 3rd trimester of pregnancy during the period from September 2008 to September 2010. Results: Out of 9972 deliveries, 49 patients were admitted with jaundice in 3rd trimester of pregnancy. Out of them 91.1% patients delivered. Vaginal delivery occurred in 82.2% and Cesarean section done in 17.7%. Preterm delivery occurred in 68.8%, low birth weight (LBW) was found in 82.2%, perinatal mortality occurred in 34.6% and maternal mortality occurred in 16.3% of patients. Conclusions: Jaundice in 3rd trimester of pregnancy leads to preterm delivery, fetal distress, intra uterine fetal death (IUFD) and high perinatal & maternal morbidity and mortality. Early diagnosis & aggressive management at tertiary care center help in reducing maternal & perinatal morbiditiy and mortality.